A descriptive study on the perceived quality of life of selected fecal-elimination-ostomy patients in a Philippine tertiary hospital - Comia, Marrah Angela F.; Asplico, Evanelle T.; Balagtas, Niña Blesilda M.; Briones, Rouchel Anne M.; Casas, Ma. Leonora Angelica B.; Florendo, Daniel Ernest L.; Francia, Lariza S.; Lim, Cristalyn Anne J.; Marcellana, Gwen R.; Morales, James Bryan C.; Ramos, Jeanne C.; Reyes, Clarita Emmanuelle F.; et al. (Manila College of Nursing University of the Philippines Manila, 2010)
Background: An ostomy operation involves major life changes for the patients and their families. Due to this experience, they need to undergo a lot of adjustments, affecting their perceived quality of life. This study aimed to determine the perceived quality of life of Filipino patients based on the physical, psychological, social, and spiritual domains, and the relationship of certain personal characteristics to their Quality of Life scores.
Methods: Surveys were conducted with 33 patients having ostomies being treated in a public tertiary hospital. A survey questionnaire based on a Filipino adaptation of the WHOQOL-BREF done by Pastor-Ugto (1998) and the STOMA-QOL questionnaire by Prieto, Thorsen and Juul (2005) was used. A descriptive analysis of the data was done. Spearman’s rho rank coefficient was also used to assess the relationship of quality of life and the variables: age, years of education and length of time with ostomy. Mann-Whitney U t-test on the other hand was employed to determine how gender, employment and adequacy of finances relate to quality of life and its specific domains.
Results: The greater percentage of participants (54.5%) perceives their over-all Quality of Life as FAIR, 45.5% perceive a GOOD Quality of Life while none has perceived POOR over-all Quality of Life. Using the Spearman’s rho rank coefficient, the results show that age is positively correlated with each of the four domains, and both age and years of education is positively correlated with the total Quality of Life. However, these correlations are not significant (level of significance = .05). Using the Mann-Whitney U t-test, findings show that there are no significant difference between the scores of males and females under each domain. In term; of employment, there is a significant difference between the scores of those who are employed against those who are unemployed under the psychological domain with a p-value of 0.12. For the perception of adequacy of income, a significant difference was identified in the spiritual domain with a p-value of 0.12.
Conclusion: The over-all Quality of Life among the patients with fecal elimination ostomies was FAIR to GOOD. Of the 4 domains, GOOD QOL was observed for the spiritual domain, FAIR for the physical, psychological and social domain. The only variables that were found to have a significant difference on the specific domains are employment, perception of adequacy of income and length of time of having an ostomy.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, April 2010.
Keywords: Intensive nursing experience -- Hospital-based.